Andries van Aarde"s Matthew Interpretation - Roux, Jurie H. le (HTS teologiese studies, 2011)
This article focused on Andries van Aarde’s interpretation of the Gospel of Matthew. It argues that Van Aarde has changed his approach to Matthew in the course of time. At the beginning of his career he focused on structural analysis and even made a contribution to the Gattung problem from a structural perspective. Then his attention shifted to narrative criticism and social-scientific criticism. Van Aarde’s consistent narratological interpretation of Matthew enabled him to identify Matthew’s ideology and to determine the way in which it took shape on the surface structure. This narratological investigation also shed new light on, amongst others, the parables, the characters and the problem of direct and indirect discourse. To conclude the article, some critical statements with regard to the historical understanding of the Gospel of Matthew were formulated.